A comprehensive review of emergency department simulation applications for normal and disaster conditions. (May 2015) - Gul, Muhammet; Guneri, Ali Fuat
Highlights: A literature review of ED simulations for normal and disaster conditions is presented. The systematic classification covers 106 reviewed papers. It provides an insight for researchers on ED simulation modelling. Abstract: Hospital emergency departments (HEDs) are the most critical units since they undertake a vital health care mission. It is required for these departments to find out rational solution methods in case of issues occurred in normal and disaster times. Simulation is an effective method to improve policies on operational, tactical and strategic decisions about EDs. The main reasons prompting us to do this study are to reveal the importance of simulation for disaster preparedness of EDs and the innovative aspects of recent ED simulation applications unlike the available literature surveys. This systematic and comprehensive review study can provide an insight for researchers on ED simulation modeling in terms of showing current state and gaps to be focused in the future.